Study on The Effect of Soft Story on Infill RC Frames Under Seismic Effect - Bhatt, Mahesh Raj; Pradhan, Prachand Man; Jha, Sudip (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Construction practice of reinforced concrete (RC) frames infilled with unreinforced masonry is quite common now-days in urban cities in Nepal and elsewhere. Previous study shows the lateral load transfer mechanism is different than that of bare frames in infill buildings. Because of the unavoidable circumstances like elimination of central columns, elimination of infill wall in basement for parking purpose and reducing the size of frame members etc. may cause the particular story to be soft.In this study the infill RC frames with stiffness irregularity has been analysed with linear time history method using Gorkha-2015 earthquake as ground motion using structural analysis and design software (ETABS 2000 V.16). In total 8-numbers of 6-story RC infilled frames were analysed introducing the soft story in each story level respectively from basement to top. Regular frame was designed as per IS 1893:2002 load combination considering torsional effect. After analyse of bare frame, regular frame and irregular frames the global and story level seismic demand parameters were studied comparatively. Base/Story shear, Story displacement, inter-story drift and fundamental time period were the parameters compared taking regular frame as reference case.Results showed that, there is significant effect of location of irregularity on the seismic demand. The global and story level seismic demand is higher when the irregularity is introduced in bottom part of the buildings and further it showed that the lateral strength of RC frames get highly enhanced due to introductions of infill in analytical models.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 2, 2017, page:79-91